2013
DOI: 10.1128/jvi.00572-13
|View full text |Cite
|
Sign up to set email alerts
|

Prion Replication Elicits Cytopathic Changes in Differentiated Neurosphere Cultures

Abstract: bThe molecular mechanisms of prion-induced cytotoxicity remain largely obscure. Currently, only a few cell culture models have exhibited the cytopathic changes associated with prion infection. In this study, we introduced a cell culture model based on differentiated neurosphere cultures isolated from the brains of neonatal prion protein (PrP)-null mice and transgenic mice expressing murine PrP (dNP0 and dNP20 cultures). Upon exposure to mouse Chandler prions, dNP20 cultures supported the de novo formation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…mESCs were differentiated to embryoid bodies (EBs) and treated with retinoic acid (RA) as described previously (Bibel et al 2007). The culture of neuroprogenitors as neurospheres from RA-treated EBs was performed as described previously (Iwamaru et al 2013). For generation of neurons, neurospheres were dissociated and plated on laminin/poly-DL-ornithine-coated adherent plates as described previously (Bibel et al 2007).…”
Section: Neuronal Differentiation Assaymentioning
confidence: 99%
“…mESCs were differentiated to embryoid bodies (EBs) and treated with retinoic acid (RA) as described previously (Bibel et al 2007). The culture of neuroprogenitors as neurospheres from RA-treated EBs was performed as described previously (Iwamaru et al 2013). For generation of neurons, neurospheres were dissociated and plated on laminin/poly-DL-ornithine-coated adherent plates as described previously (Bibel et al 2007).…”
Section: Neuronal Differentiation Assaymentioning
confidence: 99%
“…16,17,29,30 Rodent-passaged laboratory scrapie strains (Chandler, 22L and ME7) were maintained by serial-passage into wild-type mice (ICR; Japan SLC, Hamamatsu, Japan). 38 All experiments involving animals were approved by the Animal Ethical Committee and the Animal Care and Use Committee of the National Institute of Animal Health (authorization 11-008 and 11-012).…”
Section: Scrapie Sourcesmentioning
confidence: 99%
“…We previously reported that the neurosphere cultures from transgenic mice expressing murine PrP were susceptible to prion infection after differentiation by serum-free media supplemented with N-2 factor and EGF (dNP20/ EGF cultures). 12 In the current study, despite applying the same differentiation condition as dNP20/EGF cultures, the dNP5037/EGF cultures were not susceptible to prion infection. The inconsistency in prion susceptibility between mouse PrP dNP20/EGF and cervid PrP dNP5037/EGF cultures could be related to the different transgenic mouse lines (Tga20 vs Tg5037) used for these studies, as it is known that transgene expression is influenced by genome insertion position and multipllcity.…”
Section: Discussionmentioning
confidence: 60%
“…Neurospheres were cultured from the brains of neonatal Tg5037 mice expressing the elk PrP amino acid sequence (GenBank accession no.ABS87888.1) and in PrP-deficient (PrP 0/0 ) mice harvested on the day of birth (identified as NP5037 and NP0, respectively), as described previously. 12 The neurosphere cultures were passaged in serum-free media [Dulbecco's modified Eagle's medium-nutrient F12 Ham supplemented with N-2 factors, 50 ng/ml epidermal growth factor (EGF), 50 ng/ml basic fibroblast growth factor (bFGF) and penicillin and streptomycin] more than 8 times. The single-cell suspensions of neurospheres were cultured as monolayers in 6 well plates coated with fibronectin for 4 d. The cultures were differentiated by serum-free media supplemented with N-2 factor and any one of the following growth factors; i) EGF, ii) bFGF or iii) 5% fetal bovine serum (FBS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation